Imaging cellular ultrastructures using expansion microscopy (U-ExM) - Gambarotto, Davide; Zwettler, Fabian U; Le Guennec, Maeva; Schmidt-Cernohorska, Marketa; Fortun, Denis; Borgers, Susanne; Heine, Jörn; Schloetel, Jan-Gero; Reuss, Matthias; Unser, Michael; Boyden, Edward S; Sauer, Markus; et al. (Nature methods, 2019)
Determining the structure and composition of macromolecular assemblies is a major challenge in biology. Here we describe ultrastructure expansion microscopy (U-ExM), an extension of expansion microscopy that allows the visualization of preserved ultrastructures by optical microscopy. This method allows for near-native expansion of diverse structures in vitro and in cells; when combined with super-resolution microscopy, it unveiled details of ultrastructural organization, such as centriolar chirality, that could otherwise be observed only by electron microscopy.
Keywords: mikrotubuly; Microscopy, Electron; Microtubules; stereoizomerie; fluorescenční mikroskopie; Microscopy, Fluorescence; Stereoisomerism; elektronová mikroskopie